Photodynamic diagnosis with methyl-5-aminolevulinate in squamous intraepithelial lesions of the vulva: Experimental research. - Lea Leufflen; Aurelie Francois; Julia Salleron; Catherine Barlier; Gilles Dolivet; Frederic Marchal; Lina Bezdetnaya (PLoS ONE, 2018)
The incidence of the High-grade Squamous Intraepithelial Lesion of the vulva, formerly vulvar intra-epithelial neoplasia is progressively increasing. Today, an early detection and a precise localization of vulvar lesions are still problematic issues, due to the lack of accuracy of the available diagnostic tool. A new approach is the photodynamic diagnosis based on the fluorescence detection of protoporphyrin IX (PpIX) in cancer cells after topical application of a cream of methyl amino-levulinic acid. This study aimed to evaluate the effectiveness of photodiagnosis in order to discriminate the intensity of PpIX fluorescence between vulvar tumor and healthy skin. After topical application of the cream, the fluorescence on xenografted A431 tumor and adjacent skin was non-invasively measured with optical fiber. The tumor to skin fluorescence ratios were 1.38 and 1.41 at respectively 3h and 6h after application, which were significantly higher compared to those observed before application. PpIX accumulation at different depths of the tumor was investigated by spectrofluorimetry after PpIX chemical extraction from tumor sections at 3h and 6h post-application. It was noticed at both application times that the concentration of PpIX within the tumor progressively decreased. However PpIX fluorescence was always detectable up to 2.5 mm, a depth equivalent to more than three quarters of the tumor. The tumor to exposed skin ratios of PpIX fluorescence showed a good selectivity up to1mm depth at 3h post-application and up to 1.5mm at 6h post-m-ALA. Thus, the photodynamic diagnosis using in vivo topical methyl amino-levulinic acid appears to be a promising way to detect the intraepithelial lesions of the vulva. Our results open the possibility for implementation of topical methyl amino-levulinic acid in clinical settings for recognition of vulvar high-grade squamous intraepithelial lesions.